2020
DOI: 10.3389/fpsyg.2020.01988
|View full text |Cite
|
Sign up to set email alerts
|

When the Underdog Positioning Backfires! The Effects of Ethical Transgressions on Attitudes Toward Underdog Brands

Abstract: This research investigates the novel link between consumers' support for underdog brands and their ethical expectations of such brands and finds that the underdog brand positioning may not always be beneficial. Rather, we argue that the identificationbased supporting motivation for underdog brands may backfire when the accompanying specific moral expectation is not satisfied. Study 1 demonstrates that the underdog brand falls into an ethical trap in which consumers judge the brand more harshly when ethical tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…The results confirmed that BT leads to a higher level of BB (H1) than it does to RB and demands for reparation (H2-H3), which provides a solid foundation for further studies. The significant impact of BT on perceived betrayal is in line with the study by Kim and Park (2020).…”
Section: Conclusion and Theoretical Contributionssupporting
confidence: 88%
“…The results confirmed that BT leads to a higher level of BB (H1) than it does to RB and demands for reparation (H2-H3), which provides a solid foundation for further studies. The significant impact of BT on perceived betrayal is in line with the study by Kim and Park (2020).…”
Section: Conclusion and Theoretical Contributionssupporting
confidence: 88%
“…Underdog brands are associated with high levels of external disadvantage, lack of resources, and passion/determination, whereas topdog brands are brands associated with lower levels of external disadvantage and passion/determination (Paharia et al, 2011). The categorization of underdog and topdog brands in terms of external disadvantage and passion/determination is frequently based on a relative comparison of brand biographies (e.g., Kao, 2019; Kim & Park, 2020; Nagar, 2020; Tang & Tsang, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Kim et al (2008) also showed that when consumers' physical or material interests are threatened, they will abandon the underdog and support the top dog. The boundary conditions (brand status, brand identification, firm characteristics, personal control, type of service providers or transgressions, product type, and psychological experience of power; e.g., Kao, 2015;Goldschmied et al, 2017;Kirmani et al, 2017;Berendt et al, 2018;Li and Zhao, 2018;Jin and Huang, 2019;Kim and Park, 2020;Tang and Tsang, 2020) of the underdog effect were also discussed.…”
Section: Underdog and Top Dog Brand Storiesmentioning
confidence: 99%
“…Although many theoretical studies and practical operations show that underdog brand stories are more acceptable to consumers, some scholars have also found that underdogs cannot be supported by consumers in any field, that some products or services are not suitable for the underdog brand story (McGinnis and Gentry, 2009;Li and Zhao, 2018) and that underdog brand positioning may not always be beneficial (Kim and Park, 2020). Kim et al (2019) announced and proved the existence of an underdog trap, warning of the side effects of underdog positioning.…”
Section: Introductionmentioning
confidence: 99%